Crystal Fire: The invention of the transistor and the birth of the information age - Riordan, Michael; Hoddeson, Lillian (New York W.W. Norton & Company, 1997)
On December 16, 1947, John Bardeen and Walter Brattain, physicists at Bell Laboratories, jabbed two electrodes into a sliver of the metalloid geranium. The power flowing from the geranium far exceeded what went in; in that moment the transistor was invented and the Information Age was born. No other devices have been as crucial to modern life as the transistor and the microchip it spawned. This is the story of the science and personalities that made these inventions possible. William Shockley, Bell Labs' team leader and co-recipient of the Nobel Prize with Brattain and Bardeen for the discovery, grew obsessed with the transistor and went on to become the father of Silicon Valley. The process of invention - including the competition and economic aspirations involved - all part of the greatest technological explosion in history is surveyed here.